2021
DOI: 10.1111/jfpp.15358
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of probiotics enriched Chinese yam snacks produced using infrared‐assisted spouted bed drying

Abstract: A novel infrared‐assisted spouted bed drying (IRSBD) was adopted in this work to produce probiotics enriched Chinese yam snacks with high quality. The effects of drying temperature (30°C, 40°C, 50°C, 60°C, and 70°C) and airflow speed (16, 19, 22, 25, and 28 m/s) on drying characteristics, probiotics retention as well as storage stability and physical‐chemical qualities of yam snacks were studied. Results showed that the higher drying temperature and higher airflow speed were beneficial to shorten the drying ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Some tubers such as Chinese yam or yacon have also recently been used as new carriers for probiotics. Li et al (2021b) applied novel infrared-assisted jet bed drying (IRD) to produce probiotic Chinese yam snacks, which is a kind of medicinal and edible product in China. Different drying temperatures (from 30 to 70 °C) and airflow speeds (from 16 to 28 m s À1 ) were evaluated, best results being obtained at 40 °C and an airflow speed of 22 m s À1 .…”
Section: Vegetable-based Snacksmentioning
confidence: 99%
“…Some tubers such as Chinese yam or yacon have also recently been used as new carriers for probiotics. Li et al (2021b) applied novel infrared-assisted jet bed drying (IRD) to produce probiotic Chinese yam snacks, which is a kind of medicinal and edible product in China. Different drying temperatures (from 30 to 70 °C) and airflow speeds (from 16 to 28 m s À1 ) were evaluated, best results being obtained at 40 °C and an airflow speed of 22 m s À1 .…”
Section: Vegetable-based Snacksmentioning
confidence: 99%
“…Uniform drying is provided by the thorough mixing of the materials produced by the jet fluidization while the energy consumption is reduced by the efficient heating assisted with IR. In our previous work, IRSBD was used for different agricultural products, which improved dried products' quality and reduced energy consumption 13,14 . Regarding the effect of temperature and airflow rate of IRSBD, studies have shown that drying temperature is a key factor in determining drying efficiency and product quality.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, IRSBD was used for different agricultural products, which improved dried products' quality and reduced energy consumption. 13,14 Regarding the effect of temperature and airflow rate of IRSBD, studies have shown that drying temperature is a key factor in determining drying efficiency and product quality. An increase in drying temperature leads to an improvement in drying efficiency but its effect on product quality is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…apple 108,111–114 and strawberry 35 ) and tubers (e.g. yam) 115 . Probiotics were mostly incorporated by impregnation (soaking food pieces in a probiotic solution) at atmospheric pressure 35,108,113 or under vacuum 112,115 prior to drying.…”
Section: Introductionmentioning
confidence: 99%
“…yam) 115 . Probiotics were mostly incorporated by impregnation (soaking food pieces in a probiotic solution) at atmospheric pressure 35,108,113 or under vacuum 112,115 prior to drying. Encapsulated probiotics were reported to survive better than their free counterparts during drying and during passage through the gastrointestinal tract 114 .…”
Section: Introductionmentioning
confidence: 99%